QTL analysis for yield related traits using populations derived from an indica-japonica hybrid in rice (Oryza sativaL.) - Lutfor Rahman; Most Sakina Khanam; Hee-Jong Koh (Czech Journal of Genetics and Plant Breeding, 2008)
Introgression has been achieved from a wild species Oryza minuta (2n = 48, BBCC, Acc No.101141) into O. sativa subsp. indica IR71033-121-15. This introgression line was developed at International Rice Research Institute (IRRI) through embryo rescue as well as three backcrosses using IR31917-45-3-2 as a recurrent parent. These two IR lines resemble each other but differ in several important agronomic traits, which can be attributable to O. minuta introgressions. Out of 530 STS markers tested for introgression analysis, at least 14 introgressed chromosomal segments from O. minuta were detected throughout 12 chromosomes. Most of the introgressed segments were quite small in size, as they were detected by single markers and flanking markers were negative for introgressions. A population from the cross between japonica cultivar Junambyeo and introgressed indica line IR71033-121-15, consisting of 146 plants, was evaluated for ten agronomic traits. Genotyping of F2 lines and phenotyping from both F2 and F3 were considered for QTL analysis. A total of 11 single-locus QTLs (S-QTLs) were identified for ten traits, i.e. days to heading (DTH), panicle number (PN), spikelet fertility (SF), panicle length (PL), spikelet per panicle (SPP), grain length (GL), grain width (GW), grain length to width ratio (GLW) and grain thickness (GT) in both populations. The O. minuta derived alleles of QTLs, spp6, gl3, glw3, glw5 and t12 were detected in both populations indicating robust QTLs for these traits. QTLs from O. minuta introgression could be new sources of natural genetic variation for genetic improvement of rice.